RNase H eliminates R‐loops that disrupt DNA replication but is nonessential for efficient DSB repair. (5th April 2018) - Zhao, Hongchang; Zhu, Min; Limbo, Oliver; Russell, Paul
Abstract: In Saccharomyces cerevisiae, genome stability depends on RNases H1 and H2, which remove ribonucleotides from DNA and eliminate RNA–DNA hybrids (R‐loops). In Schizosaccharomyces pombe, RNase H enzymes were reported to process RNA–DNA hybrids produced at a double‐strand break (DSB) generated by I‐PpoI meganuclease. However, it is unclear if RNase H is generally required for efficient DSB repair in fission yeast, or whether it has other genome protection roles. Here, we show that S. pombe rnh1∆ rnh201∆ cells, which lack the RNase H enzymes, accumulate R‐loops and activate DNA damage checkpoints. Their viability requires critical DSB repair proteins and Mus81, which resolves DNA junctions formed during repair of broken replication forks. "Dirty" DSBs generated by ionizing radiation, as well as a "clean" DSB at a broken replication fork, are efficiently repaired in the absence of RNase H. RNA–DNA hybrids are not detected at a reparable DSB formed by fork collapse. We conclude that unprocessed R‐loops collapse replication forks in rnh1∆ rnh201∆ cells, but RNase H is not generally required for efficient DSB repair. Synopsis: Yeast cells lacking RNases H1 and H2 accumulate RNA–DNA hybrids that trigger replication fork collapse, but RNases H1/H2 are not generally required for efficient double‐strand break repair. RNase H1/H2‐deficient cells are fully able to repair double‐strand breaks formed by ionizing radiation. RNase H1/H2 mutants accumulate RNA–DNA hybrids at tRNA and rDNA genes but not at an efficiently repaired double‐strand break. Recombinational repair proteins, Mus81 resolvase and Rad3/ATR‐Chk1 checkpoint proteins are crucial for cellular survival in the absence of RNases H1/H2. Abstract : Yeast cells lacking RNases H1 and H2 accumulate RNA–DNA hybrids that trigger replication fork collapse, but RNases H1/H2 are not generally required for efficient double‐strand break repair.